Predictors of Sex-Induced Crisis, Sexual Function and Marital Satisfaction in Women With Sickle Cell Disease - Adesoye, Oluwatosin B.; Akhigbe, Roland E. (Journal of sexual medicine, 2022)
Sex-induced and orgasm-induced crisis, sexual dysfunction, and marital satisfaction among women with sickle cell disease (SCD) is under-reported. This study assessed sexual function in women with SCD and compared sexual function in women with SCD to women without SCD. This was a descriptive and comparative cross-sectional survey that involved 435 women with SCD and 406 women without SCD (as controls). This study demonstrates the predictors of sex-induced crisis, sexual function and marital satisfaction in women with sickle cell disease. The prevalence of dyspareunia and marital dissatisfaction was higher in women with SCD than those without SCD. In addition, SCD was significantly associated with multiple sexual dysfunctions, with reported symptoms of sexual desire disorder (HSDD), female sexual arousal disorder (FSAD), and female sexual orgasm disorder (FSOD). Genotype, age, age at puberty, dyspareunia, and duration of infertility were the observed independent predictors of sexual dysfunction in women with SCD. Also, most (54.02%) of the SCD subjects experienced sex-induced and orgasm-induced crises. Although water intake before and after sex was reported to be beneficial in preventing sex-induced and orgasm-induced crisis in women with SCD, it was not a predictor of sexual dysfunction. SCD patients are at risk of sex-induced and orgasm-induced crisis as well as sexual dysfunction. No study has ever reported the incidence of sex-and orgasm-induced crisis and sexual dysfunction in women with SCD. Also, we used a reasonably large sample size and utilized widely acceptable validated and reproducible tools like ENRICH Marital Satisfaction (EMS) and Female Sexual Function Index (FSFI) to assess the marital satisfaction and sexual function of the studied participants. This allows for the generalization of our findings. The limitations of the present study include recall bias and the inability to document real-time occurrences of sex-and orgasm-induced crisis and the incidence of female sexual dysfunction. Furthermore, though the risk factors of sexual dysfunction as perceived by women with SCD were elicited, biological risk factors and the possible associated mechanisms were not determined in this study. Our study shows that sex-induced and orgasm-induced crisis and sexual dysfunction are significant morbidities in women with SCD, and fluid/water intake before and after sexual activity may be beneficial. Adesoye OB, Akhigbe RE. Predictors of Sex-Induced Crisis, Sexual Function and Marital Satisfaction in Women With Sickle Cell Disease. J Sex Med 2022;19:1625–1633.